2005
DOI: 10.1590/s0073-47212005000200010
|View full text |Cite
|
Sign up to set email alerts
|

Abundância e aspectos reprodutivos de Loricariichthys platymetopon (Siluriformes, Loricariidae) em quatro trechos da represa Capivara, médio rio Paranapanema

Abstract: ABSTRACT. Abundance and reproductive aspects of Loricariichthys platymetopon (Siluriformes, Loricariidae) in four sections of the Capivara reservoir, river Paranapanema. The armored catfish Loricariichthys platymetopon was recently caught by the first time in the middle region of river Paranapanema. It has quickly become one of the most abundant species. This study evaluated reproductive aspects of 1,044 specimens collected in the Capivara reservoir. Abundance, sex ratio, RGS, IAR and oocyte diameter were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 11 publications
3
19
1
7
Order By: Relevance
“…The values for GSI also began to rise in August/September, peaking in October/November for females and August/September for males. Similar results were found in other Loricariidae in various regions of Brazil, for example, Rhinelepis aspera (Agostinho et al, 1990), Hypostomus commersonii (Agostinho et al, 1991), H. ancistroides (Viana et al, 2008), Rineloricaria latirostris (Barbieri, 1994), Loricariichthys platymetopon (Bailly et al, 2011;Marcucci et al, 2005), L. spixii (Duarte et al, 2007), among others. Males showed distinctly greater condition factor than that of females throughout the study period, probably because of higher energy expenditure of females during the maturation process (Cantanhêde et al, 2007), a feature also reported by Agostinho et al (1990) for Rhinelepis aspera in the rio Paranapanema (state of Paraná).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The values for GSI also began to rise in August/September, peaking in October/November for females and August/September for males. Similar results were found in other Loricariidae in various regions of Brazil, for example, Rhinelepis aspera (Agostinho et al, 1990), Hypostomus commersonii (Agostinho et al, 1991), H. ancistroides (Viana et al, 2008), Rineloricaria latirostris (Barbieri, 1994), Loricariichthys platymetopon (Bailly et al, 2011;Marcucci et al, 2005), L. spixii (Duarte et al, 2007), among others. Males showed distinctly greater condition factor than that of females throughout the study period, probably because of higher energy expenditure of females during the maturation process (Cantanhêde et al, 2007), a feature also reported by Agostinho et al (1990) for Rhinelepis aspera in the rio Paranapanema (state of Paraná).…”
Section: Discussionsupporting
confidence: 80%
“…In other studies with species of the genus Loricariichthys, e.g. L. platymetopon in the Paranapanema and the Paraná rivers (Marcucci et al, 2005;Bailly et al, 2011) and L. spixii in the Lajes reservoir (Duarte et al, 2007) this pattern also were observed. Although registered for some species, the 1:1 ratio is seldom found.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations